Design and Test of a Riding Pontoon Hydraulic Lotus Root Digging Machine - Ming Tu; Yitao Lin; Tao Cao; Xiang Zhang; Jun Jiao; Yong Zhou; Guozhong Zhang (Agriculture, 2022)
In order to solve the problem of high labor intensity of a traditional pontoon lotus root machine with manual pushing operation, a riding pontoon digging lotus root machine was proposed in this paper. The working principle of the digging machine was introduced, the key components were designed, and the buoyancy of the pontoon was calculated and analyzed. The performance of the digging machine was tested in a lotus root pond, the lotus root digging rate was 76%, and hydraulic flushing generated by the digging machine can disperse the soil within 30 cm under water. In addition, the best flushing effect was achieved when the number of working nozzles was controlled to three. Finally, according to the test results, the optimization measures of the hydraulic lotus root digging machine were proposed, and the CFD-DEM coupled simulation model was used to simulate and analyze the soil disturbance effect of hydraulic flushing upward from the bottom of the lotus root. The results showed the relationship between nozzle diameter, angle and hydraulic flushing depth. When the nozzle angle was fixed, the soil disturbance effect decreased with increasing flushing depth and increased with decreasing nozzle diameter. When the nozzle depth was fixed, both the diameter and the angle had a significant effect on the soil disturbance effect. When the nozzle diameter was fixed, the interaction of angle and depth had no significant effect on the soil disturbance effect.